KEANEKARAGAMAN JENIS-JENIS KAYU BAKAR DI DESA LAMPEAPI, PULAU WAWONII, SULAWESI TENGGARA - Sunarti, Siti; Rugayah, Rugayah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Fire wood is become one of the alternatif fuel to replace kerosene and gas. Becauseof the government regulation that replace kerosene into elpiji gas, many local peoplebecome prefer using fire wood for their cooking, although it cause air pollution.Twenty six plant species have been recorded as fire wood in Lampeapi, WawoniiIsland, S.E. Sulawesi. Those species collected from the beach and also hill forest.